PHYSICAL AND ACTIVITY ACTIVITY TONER OF ESSENTIAL OIL OF BAY LEAF (SYZYGIUM POLYANTHUM) AGAINST PROPIONIBACTERIUM ACNE - Anna Yusuf; Davit Nugraha; Marlina Indriastuti; Siti Rahmah KR; Laela Tri Fadila (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Indonesian people have been using natural ingredients for generations as traditional medicines to treat various diseases or as a preventative measure. One of the plants often used is bay leaf (Syzygium polyanthum). Bay leaves (Syzygium polyanthum) contain 0.2% essential oil, with methyl chavicol, eugenol, and citral as the main compounds. The purpose of this study was to determine the physical properties of essential oil toner preparations from bay leaf plants (Syzygium polyanthum) and to understand the activity of the essential oil toner preparation from bay leaf plants (Syzygium polyanthum) against Propionibacterium acnes as an acne treatment. The physical test results produced the following data: organoleptic test, thin liquid form, distinctive bay leaf smell, clear slightly cloudy color, homogeneity test all preparations were homogeneous, pH test for average F0 5.75 ± 0.5016, F1 5.62±0.1039, F2 5.70±0.08083 and F3 5.64±0.05508 all met the requirements in the pH range of 4.5-6.5. ...